The (im)possibility of being a breastfeeding working mother: experiences of Ecuadorian healthcare providers - Mendoza-Gordillo, Maria J.; Bates, Benjamin R.; Vivat, Bella (Frontiers in Communication, 2023)
Throughout the twentieth century, public health agencies and expert healthcare professionals have recognized breastfeeding as the most nutritious and appropriate option for feeding infants. the Ecuadorian government, in line with international guidelines, has therefore developed laws and initiatives to improve the initiation and maintenance of breastfeeding, especially among working mothers. However, breastfeeding rates in Ecuador are low.A qualitative methodology following social constructionist approaches was applied to explore the breastfeeding experiences of Ecuadorian women who are both mothers and healthcare professionals. Using snowball sampling, sixty healthcare professionals who breastfed their babies: twenty nurses, twenty physicians, and twenty nutritionists, took part in research interviews lasting between 30 and 92 minutes. All participants are currently offering telehealth or face-to-face consultation to their patients in Ecuador. Since Ecuador is a multicultural country, efforts were made to include participants from different regions of the country. Data gathering employed virtual semi-structured interviews including Photovoice. The interviews were carried out in Spanish, following a semistructured topic guide. The data analysis employed constant comparative methods.The analysis produced three overarching themes: Integrating breastfeeding in life and work; Establishing space for breastfeeding at work; Negotiations and tensions. The theme Integrating breastfeeding in life and work addresses participants' corporeal and emotional experiences when breastfeeding. This theme also includes the participants' experiences of how they integrated their maternal identity and adapted their breastfeeding bodies to their daily routines. the second theme: